STUDENTS’ ENGAGEMENT IN LEARNING ENGLISH VOCABULARY VIA GAMES IN KAHOOT! - Susie Kusumayanthi; Mia Rusmiyati (English Journal Literacy Utama, 2021)
This study deals with how students are involved in the use of Kahoot in learning English. The aims of this study are to investigate the students’ engagement about vocabulary using Kahoot and their interests when Kahoot! is implemented in their English classes. Kahoot! in this research is an online gamification method applied by teachers in the classroom used by students. This research employs a descriptive qualitative research. The data obtained through two main instruments, namely class observations and questionnaires. Class Observations show that Kahoot! helps students to be actively involved in learning vocabularies in English. Therefore, the use of Kahoot! in learning English is beneficial for students because it helps the student learning in variety of ways. The results of the questionnaire show that the students are interested in learning English vocabulary using Kahoot! because they do feel the benefits of using Kahoot! in their learning English as it helps them to learn better.